FINANCIAL LITERACY AND FINTECH ADOPTION AMONG UNIMAS STUDENTS - Rosman, Muhammad Solehin; Abdul Karim, Bakri; Hafeez Ur Rehman, Awais Ur Rehman; Kadri, Norlina (UNIMAS Review of Accounting and Finance, 2025)
This study investigates the relationship between financial literacy and fintech adoption among students at Universiti Malaysia Sarawak (UNIMAS). This study uses a structured questionnaire for 152 respondents. Both descriptive and regression analysis are used in this study. The regression results show that demographic factors are not significant influencing fintech adoption among UNIMAS students. On the other hand, financial knowledge, perceived usefulness and digital literacy are significant. The implications of this research extend beyond academia, holding significant relevance for policymakers and financial service providers.